Gold compounds inhibit the Ca2+-ATPase activity of brain PMCA and human neuroblastoma SH-SY5Y cells and decrease cell viability - Berrocal, Maria (2021)
Plasma membrane calcium ATPases (PMCA) are key proteins in the maintenance of calcium (Ca2+) homeostasis. Dysregulation of PMCA function is associated with several human pathologies, including neurodegenerative diseases, and, therefore, these proteins are potential drug targets to counteract those diseases. Gold compounds, namely of Au(I), are well-known for their therapeutic use in rheumatoid arthritis and other diseases for centuries. Herein, we report the ability of dichloro(2-pyridinecarboxylate)gold(III) (1), chlorotrimethylphosphinegold(I) (2), 1,3-bis(2,6-diisopropylphenyl)imidazol-2-ylidenegold(I) chloride (3), and chlorotriphenylphosphinegold(I) (4) compounds to interfere with the Ca2+-ATPase activity of pig brain purified PMCA and with membranes from SH-SY5Y neuroblastoma cell cultures. The Au(III) compound (1) inhibits PMCA activity with the IC50 value of 4.9 µM, while Au(I) compounds (2, 3, and 4) inhibit the protein activity with IC50 values of 2.8, 21, and 0.9 µM, respectively. Regarding the native substrate MgATP, gold compounds 1 and 4 showed a non-competitive type of inhibition, whereas compounds 2 and 3 showed a mixed type of inhibition. All gold complexes showed cytotoxic effects on human neuroblastoma SH-SY5Y cells, although compounds 1 and 3 were more cytotoxic than compounds 2 and 4. In summary, this work shows that both Au (I and III) compounds are high-affinity inhibitors of the Ca2+-ATPase activity in purified PMCA fractions and in membranes from SH-SY5Y human neuroblastoma cells. Additionally, they exert strong cytotoxic effects.